2020
DOI: 10.1038/s41598-020-58577-4
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional momentum-space calculation of three-body bound state in a relativistic Faddeev scheme

Abstract: In this paper, we study the relativistic effects in a three-body bound state. For this purpose, the relativistic form of the Faddeev equations is solved in momentum space as a function of the Jacobi momentum vectors without using a partial wave decomposition. The inputs for the three-dimensional Faddeev integral equation are the off-shell boost two-body t−matrices, which are calculated directly from the boost two-body interactions by solving the Lippmann-Schwinger equation. The matrix elements of the boost int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The cluster structure of light hypernuclei [53,54] has been studied with different methods, including the generator coordinate method [55], orthogonality condition model [56], Gaussian expansion method [57,58], and Tohsaki-Horiuchi-Schuck-Röpke wave function approach [59]. The Faddeev-Yakubovsky (FY) equations are extensively used to study the structure of three-and four-body bound states, with identical and non-identical particles, in different sectors of physics [60][61][62][63][64][65]. FY equations are solved with different techniques such as direct projection in momentum space [66], hyperspherical harmonics (HH) [67], adiabatic hyperspherical [68], and variational methods [69,70].…”
mentioning
confidence: 99%
“…The cluster structure of light hypernuclei [53,54] has been studied with different methods, including the generator coordinate method [55], orthogonality condition model [56], Gaussian expansion method [57,58], and Tohsaki-Horiuchi-Schuck-Röpke wave function approach [59]. The Faddeev-Yakubovsky (FY) equations are extensively used to study the structure of three-and four-body bound states, with identical and non-identical particles, in different sectors of physics [60][61][62][63][64][65]. FY equations are solved with different techniques such as direct projection in momentum space [66], hyperspherical harmonics (HH) [67], adiabatic hyperspherical [68], and variational methods [69,70].…”
mentioning
confidence: 99%
“…The definitions and notation shown in this appendix follow Refs. [19,20]. The shifted momentum arguments appearing in Eq.…”
Section: Appendix a Definitionsmentioning
confidence: 99%
“…Kamada and Glöckle have shown that relativistic and boosted potentials can be obtained directly from nonrelativistic potentials by solving a quadratic equation using an iterative scheme [18]. Once the boosted potential is obtained, the 2B T −matrix in the rest frame of the threebody system can be computed as required for the kernel of the relativistic Faddeev equations [19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we formulated the quadratic operator relation between the nonrelativistic and relativistic NN potentials in momentum space leading to a 3D integral equation 10 . We successfully implemented this iterative approach to calculate the matrix elements of boosted 2B potential from the MT potential to study the relativistic effects in a 3B bound state 11 . Our numerical results showed that the relativistic effects lead to a 2% reduction in 3B binding energy using MT potential.…”
Section: Introductionmentioning
confidence: 99%